International Experience in the Use of Transboundary Water Resources and Issues of its Regulation - Oybek, Otamirzaev (Indonesian Journal of Law and Justice, 2024)
The article analyzes the ecological problems of regulating the use of transboundary waters and its protection. The contents of the documents accepted by the international community were studied. At the same time, the state environmental policy of the Republic of Uzbekistan regarding transboundary waters and the tasks it has set for itself have been studied, and suggestions for their improvement have been given. The methods used in this research were interviews and surveys where interviews were conducted with key stakeholders, including government officials, local activists, and the general public in Uzbekistan. Use surveys to collect quantitative data about public perception and awareness regarding changing views about the value of water. In summary, effective international cooperation, clear legal regulations, the establishment of a monitoring commission, and comprehensive protection measures are essential for the sustainable management of transboundary water resources in Central Asia.